Storage of serum in plastic and glass containers may alter the serum concentration of polychlorinated biphenyls. - Karmaus, Wilfried (2004)
Valid exposure assessment and biomonitoring of toxicants rely on standardized specimen collection, handling, storage, and measurement. In a study designed to determine organochlorine concentrations in blood samples, we recruited participants from registered anglers in Michigan. After participants were interviewed, blood was collected from study subjects, either at home by a phlebotomist or in a commercial blood-draw station. The phlebotomists stored their samples in glass containers, but without our knowledge, the commercial laboratory transferred the specimens to plastic containers for freezing in its central facility. Samples were analyzed in the Analytical Chemistry Section Laboratory of the Michigan Department of Community Health. This laboratory also provided information on storage in glass (n = 28) versus plastic containers (n = 113). We conducted linear regression analyses to assess factors that may explain the concentrations of polychlorinated biphenyls (PCBs), dichlorodiphenyldichloroethylene (DDE), and polybrominated biphenyls (PBBs). Our results indicate that storage of serum in plastic containers altered the total concentrations of PCBs, in particular, the higher chlorinated PCBs (PCB-180 and PCB-199), but not DDE or PBBs. No other characteristics of the samples could explain the higher PCB values (0.75 micro g/L vs. 0.45 micro g/L; p = 0.025) of those stored in plastic containers. The proportion of PCB detects in both subsamples did not differ. Some preceding studies have provided information on whether specimens were stored in glass or plastic containers; however, a number of studies have not. We suggest the initiation of a new review process to determine whether these earlier reports were based on unbiased PCB determinations. We recommend standardizing specimen collection, handling, storage, and measurement, which is particularly necessary for newly emerging analytes.